Development and validation of a metallic haunch seismic retrofit solution for existing under-designed RC frame buildings. - Pampanin, Stefano
The feasibility and efficiency of a seismic retrofit solution for existing reinforced concrete frame systems, designed before the introduction of modern seismic-oriented design codes in the mid 1970s, is conceptually presented and experimentally investigated. A diagonal metallic haunch system is introduced at the beam?column connections to protect the joint panel zone from extensive damage and brittle shear mechanisms, while inverting the hierarchy of strength within the beam?column subassemblies and forming a plastic hinge in the beam. A complete step-by-step design procedure is suggested for the proposed retrofit strategy to achieve the desired reversal of strength hierarchy. Analytical formulations of the internal force flow at the beam?column-joint level are derived for the retrofitted joints. The study is particularly focused on exterior beam?column joints, since it is recognized that they are the most vulnerable, due to their lack of a reliable joint shear transfer mechanism. Results from an experimental program carried out to validate the concept and the design procedure are also presented. The program consisted of quasi-static cyclic tests on four exterior, ⅔ scaled, beam?column joint subassemblies, typical of pre-1970 construction practice using plain round bars with end-hooks, with limited joint transverse reinforcement and detailed without capacity design considerations. The first (control specimen) emulated the as-built connection while the three others incorporated the proposed retrofitted configurations. The experimental results demonstrated the effectiveness of the proposed solution for upgrading non-seismically designed RC frames and also confirmed the applicability of the proposed design procedure and of the analytical derivations.
Keywords: Existing buildings; Seismic retrofit; Under-designed frames; Haunch; Shear hinge; Beam?column joints